FREE CONVECTION FILM CONDENSATION OF STEAM IN THE PRESENCE OF NON-CONDENSING GASES USING CFD BASED APPROACH IN A ROOM FILLED WITH HUMID AIR - Koca, Aliihsan; Atayilmaz, Sevket Ozgur; Agra, Ozden (AMER SOC MECHANICAL ENGINEERS, 2015)
In this paper, transient natural convection combined heat and mass transfer in enclosures filled with humid air, including condensation to the walls, which are subjected to time varying prescribed temperatures, was studied numerically. Ansys Fluent CFD code implemented to the model for wall condensation from a vapor and non-condensable gas mixture. User-Defined Function (UDF) has been used to predict the condensation rate for a mixture of air and water vapor flowing past a cooled surface. The effect of the condensation process on the flow and species distribution in the vapor phase is incorporated into the flow calculations through a customized source term applied in wall-adjacent cells. The condensation phenomenon is modeled from first principles as sink terms for the mass, momentum, species and energy conservation equations. The condensation rate is obtained by requiring the condensate gas interface to be impermeable to the non-condensable gas. The Computational Fluid Dynamics (CFD) program was used to calculate the value of condensation rates, latent and sensible heat transfer rates as well as the relative humidity rates and mass fractions of species. In the study, the effects of different initial relative humidity ratios and the characteristic lengths of the condensation plate on the condensation mass fluxes were studied. The results indicated that the new system could reduce the risk of condensation on the cooling panels and provide a more comfortable indoor environment. The new system has a great potential for use in hot and humid climate regions with radiant cooling systems.
Keywords: Thermodynamics; Engineering